Contemporary Approaches to Sociological Reinterpretation of the Functions of Armed Forces - Hambardzumyan, Arevik (Journal of Sociology: Bulletin of Yerevan University, 2020)
While relatively stable, the functions of the armed forces and the ways of their implementation still undergo certain changes from time to time. This creates difficulties for their theoretical and methodological interpretation, as well as the need to rethink the concepts of the army in military sociology. The late 20th and early 21st centuries are considered by military sociologists to be a key period in terms of changing social roles, mission, functions and structure of the armed forces. The article pays special attention to theoretical approaches to their rethinking in the modern army.